From the Golem’s Jewish Myth to IBM’s responsive Watson: where are we going? - Goldfarb, Jose Luiz; Souza, Odecio (Circumscribere International Journal for the History of Science, 2018)
Since data mining uses notions from areas such as cybernetics and artificial intelligence, it is worth evoking here ages-old fears elicited by the idea of automatons created to help humans, but which eventually turned against their creators. Examples might range from the Jewish myth of the Golem to the more famous Frankenstein, Hal from Stanley Kubrick’s 2001: A Space Odyssey (1968), and the more recent Her, by Spike Jonze (2013). In this discussion we pay special attention to the fact that in the 21st-century it seems to be less a matter of creating an individual cybernetic creature, than of the rise of social networks, which are alluded by many as collective intelligence. Such collective intelligence might involve, for instance, the responsive ability of IBM’s Watson.